Peran Kepemimpinan Guru dalam Meningkatkan Kualitas Pembelajaran di Sekolah - Mila Kamalasari; Yudin Citriadin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the role of teacher leadership in enhancing the quality of learning in schools. In an ever-evolving educational context, teacher leadership emerges as a key factor in creating an effective and innovative learning environment. The research employs a case study method with a qualitative approach, involving in-depth interviews with teachers, school principals, and students from several primary and secondary schools. The findings indicate that effective teacher leadership can motivate students, enhance collaboration among peers, and encourage the implementation of more creative teaching methods. Furthermore, support from school management significantly contributes to the success of teacher leadership. These findings are expected to provide insights for the development of educational policies and leadership practices in schools